Exploring the less prominent relatives of Ficus benjamina L. in Indonesia A review on the botanical, ethnobotanical, and future perspectives of Ficus deltoidea Jack. and Ficus septica Burm.f. - Raihandhany, Reza; Zen, Tresa Variyani (Generasi Biologi Indonesia, 2022)
Ethnobotany plays a significant role in drug discovery. However, some species are often overlooked due to the lack of cultural importance. In this paper, we conducted a literature review on two lesser-known Ficus species in Indonesia, namely Ficus septica Burm.f. and Ficus deltoidea Jack. Compared to F. benjamina, these two species remain understudied. Our results showed that there are three recorded different uses of F. deltoidea and twelve of F. septica. The utilization of F. deltoidea is purely for ethnomedicine (100%), while F. septica is used for ethnomedicine (69%), culture (23%) and others (8%). The stems (50%) and the roots (50%) are the only plant parts utilized from F. deltoidea, while almost all plant parts of F. septica are utilized. Traditionally, F. deltoidea is used as an aphrodisiac, to treat internal diseases and wounds, and to increase stamina. Studies support the use of F. deltoidea as a cure for internal diseases and wounds as it has antimicrobial compounds. F. septica is traditionally used to cure boils, anthelmintic and fever for children, appendicitis, asthma, venomous snake bites, skin diseases, eye-redness, haemorrhoid, and tuberculosis. Studies support that F. septica could cure boils as its chemical compounds inhibit the growth of Staphylococcus aureus, the bacteria that cause boils. Furthermore, there are many other active compounds found in these species which are still understudied. Therefore, we conclude that F. deltoidea and F. septica have the potential to be used as modern medicine and require more in-depth research using the most advanced methods and technology.